Solabegron: a potential future addition to the β-3 adrenoceptor agonist armamentarium for the management of overactive bladder. (March 2015) - Ellsworth, Pamela; Fantasia, Jennifer
<x xml:space="preserve">Abstract</x> Introduction: Overactive bladder (OAB) affects many women and men worldwide and has a significant adverse effect on a person's quality of life. Historically, behavioral therapy and anti-muscarinic agents have been the primary therapies used in the management of OAB. However, persistence with anti-muscarinic therapy has been limited. The role of β-3 agonists is established in the management of OAB with the first β-3 agonist recently approved by the FDA. <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Solabegron&logicalOpe1=OR&field2=articletitle&text2=Solabegron&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Solabegron is one such selective β-3 agonist currently under investigation. Areas covered: In this review, the authors discuss animal studies, in vitro human bladder strip and Phase II studies, which suggest a role for solabegron in the management of OAB. The authors also discuss its potential role in combination therapy. Expert opinion: Phase II studies with solabegron support its potential future role in the management of OAB. However, further studies are needed to establish its efficacy and safety as well as to allow its clinical comparison with current therapies.